Literature Review: The Effect of Activated Carbon Adsorption on the Reduction of Iron (Fe) Concentrations in Peat Water - Yogi Chandra; Heni Sugesti; Arya Wiranata; Abdul Rohman Wali (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
Peatlands in Riau Province have great potential as a water source, but their quality often fails to meet standards due to high organic matter content and levels of heavy metals such as iron (Fe), which can pose health risks. This study aims to evaluate the effectiveness of various types of activated carbon derived from agricultural waste and biomass in reducing iron (Fe) levels in peat water through a Systematic Literature Review (SLR) based on the PRISMA 2020. A total of 8 relevant articles from the Google Scholar and ScienceDirect databases were analyzed, covering the use of materials such as empty oil palm fruit bunches, bintaro fruit shells, bamboo stalks, tofu residue, shrimp shells, corn cobs, coffee grounds, and natural zeolite. The results of the study indicate that the activation process, whether physical or chemical (using activators such as H₃PO₄, HCl, or KOH), is crucial in enhancing the porosity and surface area of activated carbon to optimize adsorption capacity. The highest iron (Fe) reduction efficiency reached 99.66% and was achieved using corn cob activated carbon activated with 0.25 M HCl at 400°C. Overall, the use of biomass waste as an adsorbent is not only effective and economical in improving peat water quality but also supports sustainable waste management.